1993
DOI: 10.1113/jphysiol.1993.sp019551
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion between distinct gating pathways of the high threshold calcium channel in rat ventricular myocytes.

Abstract: 9. Experimental testing of the predictions of the parallel pathway gating model suggests that the experimentally observed time-and voltage-dependent interconversions between the two gating pathways only occur via the closed states of the channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“…In cardiac cells, it has been reported that a channel opening similar to mode 2 gating is induced by high concentrations of 13-adrenergic agonists (Yue et al, 1990) and is probably due to the complete phosphorylation of the Ca 2+ channel protein (Ono and Fozzard, 1993). Furthermore, it has recently been shown that potentiation (increase in size of the peak amplitude and slower inactivation) of Ca 2 § current induced by repetitive depolarization (e.g., Noble and Shimoni, 1981;Mitra and Morad, 1986;Richard, Charnet, and Nerbonne, 1993) is linked to phosphorylation processes, perhaps Ca 2+ and cyclic AMP-dependent phosphorylation (Tiaho, Piot, Nargeot, and Richard, 1994). These facts have opened a possibility that mode 2-like gating mechanisms may occur even under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac cells, it has been reported that a channel opening similar to mode 2 gating is induced by high concentrations of 13-adrenergic agonists (Yue et al, 1990) and is probably due to the complete phosphorylation of the Ca 2+ channel protein (Ono and Fozzard, 1993). Furthermore, it has recently been shown that potentiation (increase in size of the peak amplitude and slower inactivation) of Ca 2 § current induced by repetitive depolarization (e.g., Noble and Shimoni, 1981;Mitra and Morad, 1986;Richard, Charnet, and Nerbonne, 1993) is linked to phosphorylation processes, perhaps Ca 2+ and cyclic AMP-dependent phosphorylation (Tiaho, Piot, Nargeot, and Richard, 1994). These facts have opened a possibility that mode 2-like gating mechanisms may occur even under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This was described first in frog atrium (Noble and Shimoni, 1981), and then in rat (Richard et al, 1990;Richard et al, 1993), guinea-pig (Mitra and Morad, 1986;Lee, 1987;Fedida et al, 1988a;Fedida et al, 1988b;Zygmunt and Maylie, 1990), rabbit (Hryshko and Bers, 1990), ferret dog (Tseng, 1988) and human (Piot et al, 1996) cardiomyocytes, although a pronounced decrease of I Ca has been observed in mouse (Sipido et al, 1998b) in which the decrease might reflect insufficient time to recover from voltage dependent inactivation.…”
Section: Facilitationmentioning
confidence: 98%
“…Repetitive depolarization, for example, produces channel inactivation when cells are stimulated from depolarized membrane holding potentials (Mitchell, Powell, Terrar & Twist, 1985;Fedida, Noble & Spindler, 1988a, b;Peineau, Garnier & Argibay, 1992;Richard, Charnet & Nerbonne, 1993). Ca2"-dependent inactivation (Mitchell et al 1985) or incomplete voltagedependent reactivation (Hryshko & Bers, 1990;Peineau et al 1992;Richard et al 1993) of Ca2" channels have been suggested to account for the decrease of ICa, Alternatively, repetitive depolarization can produce potentiation of Ca2+ channel activity (Noble & Schimoni, 1981;Mitra & Morad, 1986;Lee, 1987;Fedida et al 1988a, b;Tseng, 1988;Schouten & Morad, 1989; Richard, Tiaho, Charnet, Nargeot & Nerbonne, 1990;Zygmunt & Maylie, 1990;Peineau et al 1992) when ICa is evoked from negative holding potentials (<-50 mV). The molecular mechanisms underlying this potentiation, known as facilitation, are also a matter of debate.…”
mentioning
confidence: 99%